Opportunities and Challenges in Developing Halal Food for Muslim Tourists in Tana Toraja: A Study on Sustainable Tourism - Madjid, Sitti Saleha; Nurwahidin, Pantja; Jan, Radlyah Hasan; Yama, Arifeen (Jurnal Ilmiah Al-Syir'ah, 2024)
This study aims to identify the opportunities and challenges in developing halal food offerings for Muslim tourists in Tana Toraja, Indonesia, an area predominantly inhabited by a non-Muslim population. The primary challenges identified include a limited supply of halal raw materials, the region's image as a halal tourism destination, and a lack of awareness regarding the importance of halal certification among the local community. This qualitative study employs a case study approach, utilizing data collected through interviews, observations, and documentation from key players in the halal culinary industry in Toraja. The data were analyzed using NVivo 12 Plus, with features such as Crosstab Query and Word Cloud for data presentation. The findings reveal significant opportunities in the halal food market, driven by growing demand from Muslim tourists, menu diversification, and advancements in technology and e-commerce, which facilitate the promotion of halal products. Despite the challenges, the development of halal food offerings in Toraja can contribute to sustainable tourism through increased public awareness and collaboration between the government and the business sector, alongside halal training and certification for industry players. This study provides recommendations for the strategic development of the halal food industry as a key component of halal tourism potential in Toraja.